TAMAN POSYANDU AS INTEGRATED PUBLIC HEALTH PROGRAM - Elisa Febrianti (Universitas Airlangga, 2018)
Taman Posyandu is a form of Community-Based Health Effort (UKBM) that develops an integration model such as Integrated Service Post (Posyandu, Early Childhood Education (PAUD) and family building of children under five years old (BKB). These three components of ministers coordinate and work together. This study aims to find out the description of TamanPosyandu Cahaya Bangsa Kelurahan Medokan Semampir, Sukolilo Surabaya. The method in this research is qualitative descriptive. The result of this research is Taman Posyandu Cahaya Bangsa has been in accordance with the guidance of the implementation of Taman Posyandu. PAUD and Posyandu activities have been running very well. However, BKB activities are still not maximized in service aspect. Health promotion strategies undertaken by Taman Posyandu Cahaya Bangsa are the empowerment, development of atmosphere and partnership. The empowerment of the Taman Posyandu Cahaya Bangsa has reached phase 3 because the target of empowerment has been able to innovate and be creative. Taman Posyandu Cahaya Bangsa has done the activity of developing atmosphere individually and group. Taman Posyandu Cahaya Bangsa partnered with Dinas Kesehatan Surabaya, Puskesmas Keputih, Midwife Village, Health Promotion, PERSAGI, HIMPAUDI and PKK.. Keyword: Taman Posyandu, Posyandu, BKB, PAUD, Surabaya